PENGARUH PENGALAMAN MEREK DAN CITRA MEREK TERHADAP KEPUASAN MAHASISWA FAKULTAS EKONOMI UNIVERSITAS TADULAKO MENGGUNAKAN BEAUTY BALM (BB) CREAM WARDAH - LEONARD, AGNESIA (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2018)
The purpose of this research is to know and analyze: (1) the influence of brand experience and brand image simultaneously to the satisfaction of students of Faculty of Economics of Tadulako University using BB Cream Wardah (2) brand experience have partially influence to student's satisfaction and (3) brand image influence partial to student satisfaction. Population in research is student of Faculty of Economics of University of Tadulako which have used BB Cream Wardah product 2-3 times. Sampling technique in this study using purposive sampling, with the number of samples as many as 60 students. Data collection using questionnaires. The analytical method used multiple linear regression analysis using SPSS release 16. The result of research shows that (1) There is influence of brand experience and brand image to the satisfaction of Student of Faculty of Economics of Tadulako University using Beauty Balm (BB) Cream Wardah, (2) There is influence of brand experience to satisfaction of Student of Faculty of Economics of Tadulako University using Beauty Balm (BB) Cream Wardah, (3) There is influence of brand image to the satisfaction of Student of Faculty of Economics of Tadulako University using Beauty Balm (BB) Cream Wardah.